Experimental study of artesunate ameliorating head-and-neck radiation-induced skin fibrosis in rats through inhibiting Stat3/TGF-β1 signaling pathway - TANG Chan; OU Jianbo; NONG Xiaolin (Guangxi Yike Daxue xuebao)
Objective To study the effect and mechanism of artesunate (ART) in improving radiation-induced skin fibrosis (RISF) induced by head-and-neck radiotherapy in rats. Methods Thirty Sprague-Dawley rats were randomly divided into three groups: a control group, an irradiation only group (IR group), and an ART intervention group (ART+IR group), with 10 rats in each group. A rat model of head-and-neck radiotherapy was established by using medical linear electron accelerator with a single dose of 18 Gy. The ART+IR group was administered ART (20 mg/kg) intragastrically once a day, 3 days prior to radiation and continued for 4 weeks. Twelve weeks after the model establishment, rats were sacrificed and tissue collected. Hematoxylin-eosin (HE) staining, Masson staining and immunohistochemical staining were used to observe the histopathological condition of the skin tissue in the irradiated area of the rats, the changes of the dermal thickness, and the expression of α-SMA protein in the skin tissue; the mRNA expression of Stat3, TGF-β1, and interleukin-6 (IL-6) was detected by reverse transcription-quantitative polymerase chain reaction (RT-qPCR); the western blotting was used to detect the protein expression of p-Stat3, Stat3, TGF-β1, α-SMA, and IL-6. Results ART intervention reduced skin appearance damage, pathological damage, improved dermal thickness and collagen deposition in head-and-neck radiotherapy rats (P < 0.05), and reduced α -SMA expression in skin tissue of rats after radiotherapy; it significantly down-regulated the protein and mRNA expression levels of p-Stat3/Stat3, TGF-β1, and IL-6 (P < 0.05). Conclusion ART can improve RISF after head-and-neck radiotherapy in rats, and its mechanism may be related to the downregulation of Stat3/TGF-β1 signaling pathway and thus inhibit inflammation.